2017
DOI: 10.1007/s00464-017-5654-2
|View full text |Cite
|
Sign up to set email alerts
|

The learning effect of using stereoscopic vision in the early phase of laparoscopic surgical training for novices

Abstract: BackgroundRecently to improve depth perception, the performance of three-dimensional (3D) laparoscopic surgeries has increased. However, the effects of laparoscopic training using 3D are still unclear. This study aimed to clarify the effects of using a 3D monitor among novices in the early phase of training.MethodsParticipants were 40 novices who had never performed laparoscopic surgery (20 medical students and 20 junior residents). Three laparoscopic phantom tasks (task 1: touching markers on a flat disk with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
4
11
0
3
Order By: Relevance
“…6 Surveys among surgeons have shown a subjective decrease in cognitive workload during stereoscopic vision in comparison with monoscopic vision, but other studies also demonstrate improved objective parameters such as an increased efficiency and a reduction in the number of errors in simulated laparoscopic tasks. 7,8 Interestingly, in novice surgical trainees, task performance seems to be enhanced during the learning curve when the monoscopic view is switched to a stereoscopic view and diminished when the reverse is done, 9 an observation that is in line with the observations of Wainman et al…”
supporting
confidence: 76%
See 1 more Smart Citation
“…6 Surveys among surgeons have shown a subjective decrease in cognitive workload during stereoscopic vision in comparison with monoscopic vision, but other studies also demonstrate improved objective parameters such as an increased efficiency and a reduction in the number of errors in simulated laparoscopic tasks. 7,8 Interestingly, in novice surgical trainees, task performance seems to be enhanced during the learning curve when the monoscopic view is switched to a stereoscopic view and diminished when the reverse is done, 9 an observation that is in line with the observations of Wainman et al…”
supporting
confidence: 76%
“…monoscopic view is switched to a stereoscopic view and diminished when the reverse is done, an observation that is in line with the observations of Wainman et al. One could raise the question, on the basis of the study results of Wainman et al, whether a stereoscopic view could compensate for a low visual spatial ability test score in laparoscopic tasks.…”
supporting
confidence: 69%
“…faster completion times and fewer errors) can be achieved when novices use a 3D viewing mode rather than a 2D display or viewing mode [6][7][8][9]. However, several studies identified that the superior skill acquisition associated with training in 3D was not reflected in subsequent performance during testing in 2D [7,[10][11][12]. Further, those trained in 2D performed at a superior level when subsequently tested in 3D [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies identified that the superior skill acquisition associated with training in 3D was not reflected in subsequent performance during testing in 2D [7,[10][11][12]. Further, those trained in 2D performed at a superior level when subsequently tested in 3D [7,[10][11][12]. Such results have been interpreted as an indication of ineffective skill transfer from 3D to 2D, and effective or increased skill transfer from 2D to 3D [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation